The Effect of The Characteristics of Product Innovation on Intention to Adopt Application-Based Motorcycle Taxi Service (Go-Jek) The Moderating role of Consumer Demographic Characteristic in Yogyakarta - Rasyid, Muhammad Zakiyyul Fuad; Al Faridho Awwal, Muhammad (IJBLE Scientific Publications Community Inc., 2024)
Application-based motorcycle taxi (ojek) service becomes one of the most popular startup businesses in the recent years. There are many emerged companies that offer application-based transportation service, one of them is PT. Go-Jek Indonesia. However, there are only few researches that examine factors that might influence companies to design suitable and user-friendly application-based transportation service. This study aims to determine the influence of the characteristics of product innovation on intention to adopt app-based ojek service (Go-Jek) in which consumer demographic characteristics variable is used as moderators. Primary data were collected through questionnaires with a sample size of 280 respondents. This research used multiple regression analysis on millennial, non-millennial, and combined generations, and conducted moderate regression analysis of characteristics of an innovation (relative advantage, compatibility, complexity, trialability, observability). The result shows that relative advantage, compatibility, trialability, observability in the millennial generation have positive and significant effect on intention to adopt, whereas complexity variable has no significant effect. It was found that variables of relative advantage, trialability, and observability in the non-millennial generation have positive and significant effect, whereas complexity variable has negative effect on intention to adopt. On the other hand, the result proves that compatibility variable has no significant effect. In addition, the result also shows that variables of relative advantage, compatibility, trialability, and observability in combined generations have positive effect on intention to adopt Go-Jek application, whilst complexity variable has a negative effect on intention to adopt Go-Jek app. Factor of generation shows that the effect of variable of characteristics of an innovation (relative advantage, compatibility, complexity, trialability, observability) has stronger effect on intention to adopt in non-millennial compared with millennial generation.